Impact of 24-h feed, water, or feed and water deprivation on feed intake, metabolic, and inflammatory responses in beef heifers - Marques, Rodrigo S.; Bohnert, David W.; De Sousa, Osvaldo A. [UNESP]; Brandão, Alice P.; Schumaher, Thiago F. [UNESP]; Schubach, Kelsey M.; Vilela, Marina P.; Rett, Bruna [UNESP]; Cooke, Reinaldo F. (Oxford University Press (OUP), 2019)
This experiment investigated the effects of 24-h feed or water deprivation on hay intake, metabolic, and inflammatory responses in growing beef heifers. Forty Angus × Hereford heifers were ranked by initial BW (275 ± 6 kg) and age (278 ± 6 d) and randomly allocated to 20 drylot pens (2 heifers/pen). Pens were randomly assigned to 1 of 5 squares (4 × 4; 4 pens/square; a total of 8 animals per square), that were run simultaneously with each containing 4 experimental periods of 17 d each (day-6 to 10). From day-5 to 0 of each period, pens were offered alfalfa-grass hay ad libitum + 454 g of dried distillers grains with solubles (as-fed basis) per heifer daily. On day 0 of each period, pens received 1 of 4 treatments: 1) feed and water deprivation for 24 h (FWD), 2) feed deprivation for 24 h, but regular access to water (FD), 3) water deprivation for 24 h, but regular access to feed (WD), or 4) regular access to feed and water (CON). Treatments were concurrently applied from day 0 to 1. Heifer full BW was collected on day-6 and-5, before (day 0) and after (day 1) treatment application, and on day 3, 6, 9, and 10 of each period. Hay DMI was recorded daily from day-5 to 10. Blood samples were collected on day-5, 0, 1, 3, 6, and 10 of each experimental period. Following treatment application on day 1, BW loss was greater, and BW was less (P < 0.01) in WD, FWD, and FD compared with CON heifers, and similar (P = 0.64) among FWD and FD heifers. No treatment effects were detected (P ≥ 0.21) for final BW and overall ADG. Plasma cortisol concentrations were greater (P < 0.01) in FD and FWD vs. WD and CON on day 1, whereas FD had greater (P < 0.01) plasma cortisol concentration vs. CON, WD, and FWD on day 6 and 10. Serum NEFA concentration was greater (P < 0.01) in FD and FWD vs. WD and CON on day 1, and greater (P < 0.01) in WD vs. CON heifers on day 1. No treatment effects were detected (P = 0.53) for plasma haptoglobin concentration. Plasma ceruloplasmin concentration was greater (P < 0.01) in FD and FWD vs. CON on day 1, and greater (P < 0.01) in FD vs. CON and WD on day 3 and 6. Collectively, feed or water deprivation for 24 h did not impact feed intake and BW gain, whereas metabolic results suggest that feed deprivation stimulates cortisol, NEFA, and ceruloplasmin responses in growing beef heifers.
Keywords: beef heifers; cortisol; feed and water deprivation; hay intake; metabolic response